On the correct publishing dates of fascicules XVI - XIX of Germar's Fauna Insectorum Europae, and nomenclatorial consequences for some Dytiscidae taxa (Insecta: Coleoptera: Dytiscidae). - Fery, Hans (Contributions to Entomology = Beiträge zur Entomologie, 2007)
It is shown that fascicules XVI and XVII of Germar’s Fauna Insectorum Europae must be dated to 1834, not 1836 (Evenhuis 1997) or 1837 (Galewski 1976, Ádám 1996). Fascicule XVIII was dated to 1837 by some authors, and fascicule XIX was dated to 1836; Evenhuis (1997) dated the former to 1836 and the latter to 1837, and his view is confirmed in the present work.It follows from dating fascicule XVI to 1834 that the name Hydroporus platynotus Germar (today in the genus Deronectes Sharp), which otherwise would be a junior subjective synonym and junior primary homonym of Hydroporus platynotus Lacordaire, 1835, can be accepted as valid. In addition, the year 1834 must be accepted for the name Hydroporus blandus Germar, which is a junior subjective synonym of Hydroporus enneagrammus Ahrens, 1833 (today in genus Hygrotus Stephens). Evenhuis’s (1997) dating of fascicule XVIII to 1836 attracts attention to a third taxon, Hydroporus fenestratus (today in genus Nebrioporus Régimbart), which has been attributed to Aubé by all entomologists for over 110 years, because Aubé’s work was assumed to have been published entirely in 1836. Guignot (1932) actually dated the relevant part of that work to 1838, and it was later overlooked that this species had already been described by Germar (1836: t. 3). It is proposed to continue to use the specific name fenestratus, but with the author being Germar and the year 1836, since Article 23.9 of the ICZN cannot be applied here, and, furthermore, the stability of the nomenclature does not seem to be endangered, because only the author of the name is changed, not the name itself. - The dating of the diverse fascicules of Germar’s work may also have consequences on some insect taxa that belong neither to Dytiscidae nor to Coleoptera; this, however, cannot be commented on appropriately in the present work.KeywordsInsecta, Coleoptera, Dytiscidae, Deronectes, Nebrioporus, Hygrotus, publishing date, authorship, priority.